Phenotyping of elite zinc rich rice varieties for agronomic traits and grain zinc content - Tripathy, Swapan K.; Bala, Archana (MedDocs Publishers, 2021)
An experiment was carried out to explore high zinc(Zn) donors to be amenable for use as parents in zinc biofortification programme. A semi-dwarf rice breeding line IR 128773-4-4-2-2-B revealed high tillering ability, slender kernel feature (KL ≥ 8.0 and KL/KB˃ 4.0), acceptable grain filling (fertility%) with maturity duration 120-125 days. It had shown significantly higher yield than Swarna (Check), while BRRI Dhan 72 and DRR Dhan 45 were at par to this check variety. IR 128773-4-4-2-2-B and few local land races (Malliphulajhuli, Nikipankhia and Tikimahsuri) exceeded 40 ppm grain zinc content. Among these, IR 128773-4-4-2-2-B seem to have merit for use as zinc dense donor parent owing to its excellent agronomic features coupled with high grain zinc content.